1990
DOI: 10.1111/j.1476-5381.1990.tb12712.x
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin‐induced vasoconstriction of rat mesenteric arteries precontracted with noradrenaline

Abstract: 1 Administration of bradykinin caused dose-dependent vasoconstriction in rat isolated perfused mesenteric arteries precontracted with noradrenaline.2 The vasoconstrictor response was not mediated by BK1-bradykinin receptors.3 Inhibition of cyclo-oxygenase with indomethacin, aspirin or meclofenamate abolished the vasoconstrictor effect of bradykinin, showing that a member of the arachidonic acid cascade may be involved. 4 Inhibitors of thromboxane synthesis (imidazole and UK 38485) did not affect or only reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…It is generally acknowledged that the activation of B 1 receptors located on smooth muscle cells leads to the contraction of various types of vascular tissues, including rat mesenteric artery (Fasciolo et al, 1990) and rabbit mesenteric artery and aorta (Churchill & Ward, 1987;Levesque et al, 1993). The B 1 receptor-mediated vasoconstriction is endothelium independent and not mediated by prostaglandins (Regoli et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally acknowledged that the activation of B 1 receptors located on smooth muscle cells leads to the contraction of various types of vascular tissues, including rat mesenteric artery (Fasciolo et al, 1990) and rabbit mesenteric artery and aorta (Churchill & Ward, 1987;Levesque et al, 1993). The B 1 receptor-mediated vasoconstriction is endothelium independent and not mediated by prostaglandins (Regoli et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which the activation of B 2 receptors contracts vascular tissues, however, are unclear yet. Knowing that the activation of B 1 receptors located on vascular smooth muscle cells also leads to vasoconstriction (Churchill & Ward, 1987;Fasciolo et al, 1990;Levesque et al, 1993), the previously reported BKinduced vasoconstriction may result from the activation of B 1 receptors, instead of B 2 receptors as suggested (Fasciolo et al, 1990;Regoli & Barabe, 1980). This hypothesis is supported by the observation that both B 1 and B 2 receptors may co-exist in the same vascular tissues .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, this finding strongly suggests that PGH 2 is responsible for the bradykinin-induced endotheliumindependent vasoconstriction in the rat mesenteric artery. Bradykinin has been shown to cause vasoconstriction (10,24,25). The bradykinin-induced vasoconstrictor response has been reported to be endothelium-independent and indomethacin-sensitive or mediated by bradykinin B 2 receptors located in the vascular smooth-muscle layer (2,9).…”
Section: Discussionmentioning
confidence: 99%
“…To remove the vascular endothelium, preparations with resting tone were perfused with a 1.80 mg / mL solution of sodium deoxycholate (SD) in saline for 30 s. This caused a transient increase (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) in perfusion pressure. Then, the preparations were rinsed with SD-free Krebs solution for 40 min.…”
Section: Chemical Removal Of Vascular Endotheliummentioning
confidence: 99%